Comparison of GenesWell BCT Score With Oncotype DX Recurrence Score for Risk Classification in Asian Women With Hormone Receptor-Positive, HER2-Negative Early Breast Cancer - Kwon, Mi Jeong; Lee, Jeong Eon; Jeong, Joon; Woo, Sang Uk; Han, Jinil; Kang, Byeong-il; Kim, Jee-Eun; Moon, Youngho; Lee, Sae Byul; Lee, Seonghoon; Choi, Yoon-La; Kwon, Youngmi; et al. (Frontiers in Oncology, 2019)
Introduction: The GenesWell Breast Cancer Test (BCT) is a recently developed multigene assay that predicts the risk of distant recurrence in patients with early breast cancer. Here, we analyzed the concordance of the BCT score with the Oncotype DX recurrence score (RS) for risk stratification in Asian patients with pN0-N1, hormone receptor-positive, human epidermal growth factor receptor 2 (HER2)-negative breast cancer. Methods: Formalin-fixed, paraffin-embedded breast cancer tissues previously analyzed using the Oncotype DX test were assessed using the GenesWell BCT test. The risk stratification by the two tests was then compared. Results: A total of 771 patients from five institutions in Korea were analyzed. According to the BCT score, 527 (68.4%) patients were classified as low risk and 244 (31.6%) as high risk. Meanwhile, 134 (17.4%), 516 (66.9%), and 121 (15.7%) patients were categorized into the low-, intermediate-, and high-risk groups, respectively, according to the RS ranges used in the TAILORx. The BCT high-risk group was significantly associated with advanced lymph node status, whereas no association between RS risk groups and nodal status was observed. The concordance between the two risk stratification methods in the overall population was 71.9% when the RS low-risk and intermediate-risk groups were combined into one group. However, poor concordance was observed in patients aged <=50 years and in those with lymph node-positive breast cancer. Conclusions: The concordance between the BCT score and RS was low in women aged <=50 years or with lymph node-positive breast cancer. Further studies are necessary to identify more accurate tests for predicting prognosis and chemotherapy benefit in this subpopulation.